The Influence of Museum Virtual Tours on Students' Historical Thinking Skills in Eleventh-Grade History Subject at SMAN 13 Kabupaten Tangerang - Apriyani Nurhasanah; Muhammad Anggie Farizqi Prasadana; Yuni Maryuni (Tarikhuna: Journal of History and History Education, 2026)
This study aims to explain the influence of museum virtual tours on students' historical thinking skills in the 11th-grade Social Sciences (IS) History subject at SMAN 13 Tangerang Regency. The method used in this research is a pre-experimental pretest-post test design and was tested using a paired samples t-test. The sample was selected using a purposive sampling technique, and the sample used consisted of 34 students from class XI IS 2. Data was collected through field observations, interviews, and tests in the form of essay questions. The research results indicate a two-tailed significance value of 0.000, which is smaller than the significance threshold of 0.05, thereby demonstrating that the use of virtual museum tours has a significant effect on students' historical thinking skills. In conclusion, the utilization of museum virtual tours can be evaluated as an effective learning strategy, as it can foster students' active engagement and enthusiasm, which ultimately contributes to the development of their historical thinking skills and academic achievements.